IMPROVING STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXT THROUGH KNOW-WANT TO KNOW-LEARNED (KWL) STRATEGY - Astarina, Astarina; Rosnija, Eni; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to improve students? reading comprehension through Know-Want to Know-Learned (KWL) Strategy to class VIII students of SMP Negeri 1 Air Besar Kabupaten Landak in Academic Year 2015/2016. This research was conducted based on the problems found in the classroom. It was found that students had difficulties in understanding the generic structure of narrative text. This research was conducted through a Classroom Action Research in three cycles to 25 students of class VIII. In collecting the data, the researcher used observation and field notes. To analyzed the data by finding and comparing the mean score of the test in cycle 1 ,cycle 2 and cycle 3.  Based on the findings in this research, it was  found that using kWL Stategy in teaching and learning improved students? understanding on how to find the generic structur of narrative text. Besides, the presence of the things interests the students in teaching and learning in the classroom. Keywords: Improve, Reading, KWL Strategy